Traditional herbal medicine regulatory implementation in Ethiopia: a qualitative study - Usure, Rashed Edris; Kebebe, Dereje; Mekasha, Yesuneh Tefera; Hasen, Gemmechu; Chura Waritu, Nuredin; Dubale, Sileshi; Suleman, Sultan (Frontiers in Pharmacology, 2024)
Background: Approximately 80% of the Ethiopian population predominantly depends on herbal medicines for their primary healthcare needs. Nevertheless, worries regarding the safety, efficacy, and standard of herbal-based treatments have been escalating due to the lack of strong regulatory frameworks. Therefore, the study aimed to assess the presence of regulatory frameworks for traditional herbal medicines and their enforcement in Ethiopia.The qualitative-phenomenological study design was conducted from November 2021 to March 2022 G.C. The study included 25 regulatory official key informants (KIs) who work for national and regional medicine regulatory agencies, and 15 THM practitioners were purposefully selected for an in-depth interview (IDI) who work at the regional level. An in-depth interview guide was conducted through the purposive sampling technique. The collected data were analyzed using thematic content analysis techniques.The study found that the current national medicine proclamation was deemed inadequate in the regulation of traditional herbal medicine (THM). Both conventional and traditional herbal medicines were regulated by a single agency. Weak legal enforcement, a lack of government commitment and support, resource constraints, and inadequate regulatory tools are the main challenges faced in THM regulation.Overall, the study found inadequate legal frameworks and weak THM regulatory implementations in Ethiopia. Consequently, it is critical for all regulatory authorities in Ethiopia to exert their utmost efforts to effectively regulate THM.